Patterns of Suicide in the Context of COVID-19: Evidence From Three Australian States - Clapperton, Angela; Spittal, Matthew John; Dwyer, Jeremy; Garrett, Andrew; Kõlves, Kairi; Leske, Stuart; Millar, Ciara; Edwards, Bronwen; Stojcevski, Victor; Crompton, David Robert; Pirkis, Jane (Frontiers in Psychiatry, 2021)
Aims We aimed to determine whether there was a change in the number of suicides occurring in three Australian states overall, and in age and sex subgroups, during the first seven months of the COVID-19 pandemic, and to see if certain risk factors have become more prominent as contributing factors for suicide. Method Using real-time data from three state-based suicide registers, we ran multiple unadjusted and adjusted interrupted time series analyses to see if trends in monthly suicide counts changed and whether there had been an increase in suicides where relationship breakdown, financial stressors, unemployment and homelessness were recorded. Results Compared with the pre-COVID-19 period, during the COVID-19 period there was no change in the number of suicides overall. However, there was an increase in the number of young males who died by suicide in the COVID-19 period (adjusted RR 1.89 [95% CI 1.11-3.23]). The unadjusted analysis showed an increase in the number of suicides occurring in the context of unemployment in the COVID-19 period (unadjusted RR 1.53 [95% CI 1.18–1.96]) and a decrease in the number of suicides occurring in the context of relationship breakdown in the COVID-19 period (unadjusted RR 0.82 [95% CI 0.67–0.99]). However, no significant changes were identified when the models were adjusted. Conclusion The identified increase in suicide in young men indicates that the impact of the pandemic is likely unevenly distributed across populations. The increase in suicides in the context of unemployment reinforces the vital need for mitigation measures during COVID-19.